ANALISIS PELAKSANAAN REKRUTMEN KARYAWAN PADA PT. FEDERAL INTERNATIONAL FINANCE PEKANBARU (Tinjauan Kasus pada Departemen Kredit) - Irvan, Reinaldi; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Global competition is an inevitable phenomenon of the industrial world, one way to face this competition is the way the company is required to have employees who are competent and have a good performance. The role of employees is crucial for the success or failure of the company reaching target market. The company expects its employees to always have a higher performance, more process-oriented, more involved in leadership and be able to gain knowledge to add value to the company and employees are expected to make the company the right to compete with other companies. Given the important role of HR in an organization, it can not be denied there should be special attention on the problem of improving the quality of human resources. To get qualified human resources, the company is expected to carry out the recruitment process so that the quality of human resources is placed strictly in accordance with the required expertise. PT. Federal International Finance (FIF) to support the business activities of the focus group as a manufacturer and distributor Astra Honda in Indonesia, through the provision of financing facilities ownership of motorcycles manufactured and marketed by Astra. Where the results of this penelitiaan, respondents considered the implementation of recruitment at. Federal International Finance Pekanbaru can be said on both categories. Where the recruitment of seven sub-variables which involves determining the number and qualifications of candidates, filling in application forms, the implementation of an intelligence test, aptitude test execution, execution of test interview, medical test execution, and assessment of results is accepted or rejected, get good responses to the respondents. For some things there are respondents who respond less well among prospective applicants regarding the suitability of applicants with specified requirements, the implementation of the conditions of the aptitude test and the implementation of the prospective applicants medical tests.Keywords: Analysis, Implementation, Recruitment